WTO AGREEMENT ON RULES OF ORIGIN: IMPLICATIONS FOR SOUTH ASIA - Harilal, KN and Beena, PL (Centre for Development Studies-WP353, 2003)
From neutral trade policy devices employed to identity country of origin of commodities, the rules of origin are emerging as protectionist tools. Nation-states, as they are increasingly denied of conventional trade policy tools, are reasserting themselves by evolving new and less visible weapons of intervention. The misuse of rules of origin as protectionist tools is widely reported from PTAs among developed countries, such as EEC and NAFTA. More recently, non-preferential rules of origin are also being used for protectionist purpose. It is such protectionist adaptation of the rules of origin that prompted the WTO to launch the HWP to evolve common rules of origin for all countries. The present study is a critique of the harmonization work programme. The central objective of the ARO and also the HWP is to ensure that the rules of origin are employed without/ or with least trade distorting effects. But, as our study shows, it would be too optimistic to expect such an outcome from the HWP. On the contrary, even if it is successfully completed, the HWP is likely to leave considerable scope for misuse of rules of origin for protectionist purpose. Further, the new multilateral regime, even if it succeeds in establishing semblance of an order in the arena of rules of origin, is likely to have unequal effects on members. The moot question is as to whether the adopted harmonised rules match the trading interests of the developing nations. The picture emerging from our analysis of outstanding disputes is not very encouraging for the developing countries. They belong mainly to the traditional areas of western protectionism against developing countries. The fear that the developed countries are trying to manipulate rules of origin to compensate for the loss of tariff and other conventional barriers, therefore, cannot be ruled out.